A practical approach to acute vertigo. Issue 4 (21st July 2008) - Seemungal, B M; Bronstein, A M
Abstract : Patients complaining of symptoms of acute vertigo present a diagnostic challenge for the clinician; the main differential diagnoses are acute unilateral peripheral vestibulopathy ("vestibular neuritis"), cerebellar stroke or migraine. The head impulse test is useful in the acute situation because, of these three diagnostic alternatives, it will only be positive in patients with vestibular neuritis. A history of acute vertigo and hearing loss suggests Ménière's disease but the clinician must be wary of anterior inferior cerebellar artery strokes which may cause audiovestibular loss due to peripheral vestibulocochleal ischaemia, although the accompanying brainstem signs should remove diagnostic ambiguity. We also discuss other less common vertigo diagnoses that may be referred to the neurologist from the acute general hospital take. As ever in neurology, a careful history and focussed examination is necessary in the evaluation and management of acute vertigo.